A hydrazone based probe for selective sensing of Al(iii) and Al(iii)-probe complex mediated secondary sensing of PPi: framing of molecular logic circuit and memory device and computational studies. Issue 2 (20th December 2017) - Mohammad, Hasan; Islam, Abu Saleh Musha; Prodhan, Chandraday; Chaudhuri, Keya; Ali, Mahammad
Abstract : A hydrazone-based conjugate acts as a dual channel sensor towards Al 3+ and PPi in H2 O–MeOH with excellent sensing capability in live cells. Abstract : A hydrazone-based conjugateNap-hyz-pyz (H3 L 3 ) with potential N2 O2 donor atoms was found to act as a dual channel (colori- and fluori-metric) sensor towards Al 3+ and PPi in H2 O–MeOH (6 : 4, v/v) at pH 7.2 (40 mM HEPES buffer) at 25 °C. The formation constants, K f = (3.49 ± 1.77) × 10 4 and (3.78 ± 0.1) × 10 4 M −1, of the sensor towards Al 3+ were determined by absorption and fluorescence titrations, respectively. The 1 : 1 stoichiometry of the reaction was determined by Job's method and confirmed by ESI-MS + ( m / z ) studies. The LOD for Al 3+, as determined by the 3 σ method, was found to be 114.54 nM. Most strikingly, the addition of ∼115 μM PPi to theNap-hyz-pyz –Al 3+ ensemble (20 μM ligand and 74 μM Al 3+ ) leads to complete quenching of fluorescence. The fluorescence response ofNap-hyz-pyz towards Al 3+ was not perturbed by the presence of 5 equivalents or more of other ions and inorganic anions. The structure of the [Al(L 3 )(H2 O)] complex was delineated by DFT calculations. TD-DFT studies were performed to investigate various spectral transitions. Based on changes in the fluorescence intensities ofNap-hyz-pyz in the presence of Al 3+ and PPi at 487 nm, INHIBIT and molecular logic gates were constructed and interpreted. The probe was found to be bio-compatible and cell permeable with no or negligible cytotoxicity; thus, it provides a good opportunity for in vitro cell imaging studies of these ions. The presence of ATP or Pi did not interfere with the fluorescent detection of PPi. Thus, these evident and excellent sensing capabilities ofNap-hyz-pyz towards Al 3+ and PPi were further scrutinized in HepG2 cell lines.